States of (In)Security: Violence, Local Governance, and Institutionalized Arbitrariness in Northern Uganda - Tapscott, Rebecca. (2017)
Abstract: This dissertation theorizes uncertainty as a contemporary mode of rule in northern Uganda, focusing on how violence is institutionalized within and beyond the state's governing institutions. It examines the relationship between the state security apparatus and vigilante groups in and around Gulu Town, northern Uganda. The findings are based primarily on qualitative research, relying on approximately 300 interviews conducted over eight months of qualitative field research between February 2014 to February 2016. The qualitative findings are supplemented with an analysis of a 1,551 household survey. The research focuses on conflicts between local vigilantes and state security providers, primarily the police. I find that in the area of security the central Ugandan state is ever-present in citizens' imaginations. I argue that this is achieved through a strategy of rule that I have termed institutionalized arbitrariness, in which violence is institutionalized in the state's governing system, even though its use remains unpredictable from the perspective of ordinary citizens. In particular, the state unpredictably claims and denies its authority, while deploying potentially exceptional violence to quell resistance. This unpredictability fragments citizen resistance to and claim-making on the state. In this way, the ruling regime maintains control of this post-conflict frontier zone without expending the resources typically associated with direct rule, while also avoiding the principal-agent problems associated with indirect rule. Thus, institutionalized arbitrariness is an effective and efficient mode of governance, and contributes to our understanding of governance in post-colonial African states with militarized and statist regimes. The dissertation illustrates how current theory on the post-colonial sub-Saharan states relies on two faulty assumptions: that the division between public and private can be conceived of as stable, and that a mismatch between violence and governing institutions is a necessary feature of post-colonial sub-Saharan African states. Instead, Uganda's ruling regime has produced an unfamiliar match between violence and governing institutions which has allowed the regime to efficiently and effectively extend and maintain its control to the conflict-affected borderlands of the country. Thus, institutionalized arbitrariness argues for a dynamic understanding of the relationship between violence and institutional form, observing that they can be opportunistically de-coupled and re-coupled according to a wider strategy of rule. The theory of institutionalized arbitrariness contributes to debates on state formation and statecraft, neopatrimonialism, legal pluralism, and public authority. The findings suggest that "fragile" states may be stronger than they appear. Indeed, these states govern far more efficiently in terms of return on investment than a traditional welfare state. The theory also challenges a dichotomy between liberal and illiberal regimes, pointing out that successful governing strategies allow for spaces of liberalism to further broader goals of illiberal governance. Finally, it shows that institutional multiplicity cannot be viewed independently from the state, but instead must be understood in relation to the state's capacity for violence. While ordinary citizens may compete in a plural institutional environment, their competitions occur in relation to a larger power game between the ruling regime and the polity at large. An increasingly fluid and labile relationship between violence and governing institutions bodes poorly for many goals of international development and global security, including the future of liberal democracy, human welfare, and access to security and justice—and thus, it must not be ignored.; Thesis (Ph.D.)--Tufts University, 2017.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: Alex de Waal.; Committee: Jenny Aker, Dyan Mazurana, and William Reno.; Keywords: Political science, and African studies.